How can we become more equal? Public policies and parents' work-family preferences in Germany - Mareike Bünning; Lena Hipp (Journal of European Social Policy, 2022)
This study examines how public policies affect parents' preferences for a more egalitarian division of paid and unpaid work. Based on the assumption that individuals develop their preferences within a specific policy context, we examine how changes in three policies affect mothers' and fathers' work–family preferences: the availability of high-quality, affordable childcare; the right to return to a full-time job after having reduced hours to part-time and an increase in the number of `partner months' in parental leave schemes. Analysing a unique probability sample of parents with young children in Germany from 2015 (N = 1756), we find that fathers would want to work slightly fewer hours if they had the right to return to a full-time position after working part-time, and mothers would want to work slightly more hours if childcare opportunities were improved. Full-time working parents, moreover, are found to prefer fewer hours independent of the policy setting, while non-employed parents would like to work at least some hours. Last but not least, our analyses show that increasing the number of partner months in the parental leave scheme considerably increases fathers' preferences for longer and mothers' preferences for shorter leave. Increasing the number of partner months in parental schemes hence has the greatest potential to increase gender equality.
doi:10.7802/2039
Keywords: 300; work-family policies; parental leave; childcare; working time regulations; parenthood; working hours; gender equality; preferences; capabilities framework